The Role of Coping Strategy And Legal Protection on Migrant Workers: A Literature Review - Hasdianti, Fitri; Imelda, Johanna Debora (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
This paper aims to determine the role of coping strategies and legal protection on Indonesian migrant workers. By focus on coping strategies and legal protection on migrant workers. Since they are indirectly correlated and cannot be parted from Indonesian Migrant Workers. That being the case, this paper examines these two issues by conducting a literature review and portraying them descriptively. Where it is related to the condition of Indonesian Migrant Workers and the difficulties, they face in the migration process. Coping strategies, in this case, act as PMI's efforts to overcome problems or challenges in the individual and social spheres. On the other hand, legal protection plays a role as an effort by the government to protect and be responsible for the rights of its citizens. Both coping strategies and legal protections have a substantial contribution to PMI's welfare condition. In consequence, the protection of PMI does not just rely on the government, but all parties include the private sector (businesses or sponsors) and PMI themselves.